MINIMAL INVASIVE PLATE OSTEOSYNTHESIS OF CLOSE FRACTURES OF DISTAL TIBIA - Shabbir, Ghulam; Hussain, Shujaat; Nasir, Zulfiqar Ahmad; Shafi, Kamran; Khan, Javeid Ahmed (Journal of Ayub Medical College Abbottabad, 2011)
Background: The limited soft tissue, subcutaneous location and poor vascularity render the tibial fractures very challenging. Treatment of distal tibial fractures using minimally invasive plate osteosynthesis (MIPO) technique may minimise damage to soft tissues and the vascular integrity of bony fragments, leaving comminuted fragments out of the mechanical construct, preserving soft tissues with limited operative exposure. This descriptive study was conducted to assess the outcome of patients treated with MIPO technique for distal tibial fractures. Methods: Seventy three cases of multifragmentary fractures of the distal tibia admitted in Bahawal Victoria Hospitals, Bahawalpur between April 2009 and October 2010 were included in this study. Patient's outcome in terms of period of radiologic union of the fractured segments and period of full weight bearing capacity were accessed. Results: There were 66 males and 7 females of mean age 43 years. The mean follow-up period was 13 weeks. (Ranging from 9-16 weeks). All patients were fully weight bearing at 16 weeks (ranging 9-16 weeks) showing radiological union. There were two superficial infections treated successfully using oral antibiotics and no failures of fixation. There were no cases of rotational malalignment. Conclusion: MIPO is an effective method of treatment for distal tibial fractures. The use of indirect reduction techniques and small incisions is technically demanding but decreases surgical trauma to soft tissues. Keywords: Distal tibial fractures, Minimally invasive plate osteosynthesis, MIPO